Influence of National Culture and Historical Patriotic Traditions on the Formation of Military Patriotism in Youth - Rahmonov Abrorbek Rustamovich (Web of Scientist International Scientific Research Journal, 2026)
Military patriotic education encourages a person to be more loyal and devoted to his homeland, and also calls for its constant protection. The increase in the number of military patriotic youth in the country adds strength to the countryʼs strength and power. In an increasingly globalized world, the education and upbringing of youth is becoming one of the urgent tasks. Building the education of youth on the basis of national culture and historical patriotism will increase the effectiveness of education, further expand its impact and scope. At the same time, it will help young people develop feelings such as an understanding of national identity, a sense of pride in their country, and an understanding of their duty to the Motherland. The article discusses the harmony of national and universal values, their importance in the military patriotic education of young people, and the reasons for the current oblivion of national values and traditions.